EMPLOYEE'S ENGAGEMENT, WORK DISCIPLINE TOWARD WORK SATISFACTION AND ITS IMPACT ON HUMAN RESOURCE PERFORMANCE (STUDY IN JAMBI OF TRANSPORTARTION AGENCY, INDONESIA) - Sumarni Sumarni; Sry Rosita; Fitri Widiastuti (Journal of Business Studies and Management Review, 2019)
Government agencies are required to observe and manage human resources as the most important element that directly affects the effectiveness of organizational work, especially in the long term. The purpose of this research is to analyze the variable employee engagement, working discipline, job satisfaction on the performance of employees of the DISHUB Jambi. The variables to be researched are Employee's Engagement (X1), working discipline (X2), job satisfaction (X3), employee performance (Y). Research using Fishbone Diagram (fishbone diagram), data collection is done with questionnaires, observations, and interviews. Population in this study amounted to 164 employees of the DISHUB city of Jambi, the size of the samples used in this study amounted to 116 respondents, the final result was 99 respondents who submitted questionnaires to the research team. Data is further processed using SmartPLS programs. From the structural model and the loading value of the item statement, there are several indicators of variables that have a loading value below 0.5. Technical analysis involves the determination of the correlation coefficient and multiple linear regression, then the results are interpreted through the discussion, suggestions, and conclusions of the examined variables. The results gained in this study showed that in variable Employee's engagement, work discipline and job satisfaction were influential positivity and significant to the performance of employees of the DISHUB Jambi City.